2022
DOI: 10.1101/2022.01.04.22268719
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genome-wide association study of nociceptive musculoskeletal pain treatment response in UK Biobank

Abstract: Drug treatment for nociceptive musculoskeletal pain (NMP) follows a three-step analgesic ladder proposed by the World Health Organization (WHO), starting from non-steroidal anti-inflammatory drugs (NSAIDs), followed by weak or strong opioids until the pain is under control. However, effective pain treatment is challenged by inter-individual differences, and unsatisfied pain treatment response (PTR) rates ranging from 34 to 79% in those suffering from NMP. To investigate the underlying genetic component of PTR,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 109 publications
(117 reference statements)
0
2
0
Order By: Relevance
“…Further work is required including: (i) genetic epidemiology studies collecting data on more specific chronic pain diagnoses, clinical traits (e.g., pro- & anti-nociceptive phenotypes, quantitative sensory testing, 7073 medication/treatment responses 52,74 ) and epigenetic factors 75 (e.g., early life stress, physical activity); (ii) replication in other large genotyped datasets, 5,19 particularly population samples with non-European ancestry; and (iii) incorporating putative transdiagnostic subtypes and genetic risk stratification of placebo/control groups in clinical trials of chronic pain interventions. 3,4,27,52,76…”
Section: Discussionmentioning
confidence: 99%
“…Further work is required including: (i) genetic epidemiology studies collecting data on more specific chronic pain diagnoses, clinical traits (e.g., pro- & anti-nociceptive phenotypes, quantitative sensory testing, 7073 medication/treatment responses 52,74 ) and epigenetic factors 75 (e.g., early life stress, physical activity); (ii) replication in other large genotyped datasets, 5,19 particularly population samples with non-European ancestry; and (iii) incorporating putative transdiagnostic subtypes and genetic risk stratification of placebo/control groups in clinical trials of chronic pain interventions. 3,4,27,52,76…”
Section: Discussionmentioning
confidence: 99%
“…Currently available assessment tools do not allow us to determine the cause of pain; however, recent genome-wide association studies (GWAS) give insight into this by exploring the genetic underpinnings of comorbid pain conditions including EAP. A systematic review of GWAS studies for pain, which included dysmenorrhea (primary or secondary to endometriosis), found overlapping genes with temporomandibular disorder, migraine, cancer pain, musculoskeletal pain, neuraxial pain and general nociception in the Human Pain Genetics Database [23]. Earlier this year, the largest GWAS of endometriosis to date was reported, identifying two SNPs associated with pain sub-phenotypes [10…”
Section: Key Pointsmentioning
confidence: 99%